Formation, Molecular Structure, and Morphology of Humins in Biomass Conversion: Influence of Feedstock and Processing Conditions - van Zandvoort, Ilona; Wang, Yuehu; Rasrendra, Carolus B.; van Eck, Ernst R. H.; Bruijnincx, Pieter C. A.; Heeres, Hero J.; Weckhuysen, Bert M. (ChemSusChem, 2013)
Neither the routes through which humin byproducts are formed, nor their molecular structure have yet been unequivocally established. A better understanding of the formation and physicochemical properties of humins, however, would aid in making biomass conversion processes more efficient. Here, an extensive multiple‐technique‐based study of the formation, molecular structure, and morphology of humins is presented as a function of sugar feed, the presence of additives (e.g., 1,2,4‐trihydroxybenzene), and the applied processing conditions. Elemental analyses indicate that humins are formed through a dehydration pathway, with humin formation and levulinic acid yields strongly depending on the processing parameters. The addition of implied intermediates to the feedstocks showed that furan and phenol compounds formed during the acid‐catalyzed dehydration of sugars are indeed included in the humin structure. IR spectra, sheared sum projections of solid‐state 2DPASS 13C NMR spectra, and pyrolysis GC–MS data indicate that humins consist of a furan‐rich polymer network containing different oxygen functional groups. The structure is furthermore found to strongly depend on the type of feedstock. A model for the molecular structure of humins is proposed based on the data presented. Under scrutiny: Humin byproducts formed during the acid‐catalyzed dehydration of sugars are analyzed with multiple techniques to reveal a furan‐rich network formed via hydroxymethylfurfural (see picture). Within this network, the aliphatic linkages and oxygen functionalities strongly depend on the feedstock. A representative model for the molecular structure of humins is proposed.